The Effect of Content Marketing and Electronic Word of Mouth on Generation Z’s Visiting Decisions at Terasering Panyaweuyan - Solihin; Nindi Rospiana; Muhammad Fikry Januar; Dede Ibrahim Maulana; Eko Prasetyo; Imma Ismaniar (Journal of Applied Digital Business Management, 2026)
The development of digital media encourages tourism destination managers to utilize digital marketing strategies to influence visiting decisions, particularly among Generation Z. However, fluctuations in the number of visitors at Terasering Panyaweuyan indicate that visiting decisions have not been fully optimized. This study aims to examine the effect of Content Marketing and electronic word of mouth on Generation Z’s visiting decisions to Terasering Panyaweuyan. This research employed a quantitative method using a descriptive and verificative approach. The population of this study consisted of Generation Z tourists who had visited Terasering Panyaweuyan, with a sample of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using classical assumption tests, multiple linear regression analysis, coefficient of determination, t-test, and F-test with the assistance of SPSS software. The results show that Content Marketing and electronic word of mouth have a positive and significant effect, both partially and simultaneously, on Generation Z’s visiting decisions to Terasering Panyaweuyan. These findings indicate that effective digital content and positive online communication play an important role in encouraging visiting decisions among Generation Z tourists.